Antecedents and consequences of memorable experience in the airline industry: service robots versus human staff - Hwang, Jinsoo; Choe, Ja Young (Jacey); Joo, Kyuhyeon; Kim, Jinkyung Jenny (IAES International Journal of Robotics and Automation (IJRA), 2025)
The study aims to examine the type of service providers, such as service robots and human staff, as a potential moderator in the relationship between SERVQUAL and memorable experience in the airport industry. In order to verify 15 hypotheses, data were collected from 313 travelers who acquired information from service robots and 313 travelers who acquired information from human staff at the airport. The results of data analysis revealed that the five sub-dimensions of SERVQUAL, including tangibles, reliability, responsiveness, assurance, and empathy, enhance memorable experience. In addition, a memorable experience has a positive effect on customer satisfaction, which subsequently influences attitude and intention to use. In addition, the type of service providers moderated the links between i) responsiveness and memorable experience and ii) empathy and memorable experience.